How can we better inform our patients about post‐heart transplantation survival? A conditional survival analysis. Issue 11 (12th September 2021) - Clerkin, Kevin J.; Griffin, Jan M.; Fried, Justin A.; Raikhelkar, Jayant; Jain, Rashmi; Topkara, Veli K; Habal, Marlena V.; Latif, Farhana; Restaino, Susan; Colombo, Paolo C.; Takeda, Koji; Naka, Yoshifumi; et al.
Abstract: Background: Conditional survival (CS) is a dynamic method of survival analysis that provides an estimate of how an individual's future survival probability changes based on time post‐transplant, individual characteristics, and post‐transplant events. This study sought to provide post‐transplant CS probabilities for heart transplant recipients based on different prognostic variables and provide a discussion tool for the providers and the patients. Methods: Adult heart transplant recipients from January 1, 2004, through October 18, 2018, were identified in the UNOS registry. CS probabilities were calculated using data from Kaplan‐Meier survival estimates. Results: CS probability exceeded actuarial survival probability at all times post‐transplant. Women had similar short‐term, but greater long‐term CS than men at all times post‐transplant (10‐year CS 1.8‐11.5% greater [95% CI 1.2–12.9]). Patients with ECMO or a surgical BiVAD had decreased survival at the time of transplant, but their CS was indistinguishable from all others by 1‐year post‐transplant. Rejection and infection requiring hospitalization during the first year were associated with a persistently decreased CS probability. Conclusions: In this study, we report differential conditional survival outcomes based on time, patient characteristics, and clinical events post‐transplant, providing a dynamic assessment of survival. The survival probabilities will better inform patients and clinicians of future outcomes.